Human Rights for Women's Development in Multidimensional: A Step towards Gender Equality in Education - Andrey Shastri (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
Women's educational human rights and gender equality is one of the burning topics nowadays. Following the gender equality framework proposed by United Nations in its Millennium Summit in 2000 declared